Pengelolaan Izin Usaha Pemanfaatan Hutan Kemasyarakatan (IUPHKM) Koperasi Banau Bisa Maju Desa Beting Kecamatan Rangsang Pesisir, Kabupaten Kepulauan Meranti, Riau - Jaime De Andrade; Enny Insusanty*; Ika Lestari (Universitas Lancang Kuning, 2022)
Community forestry (HKm) is one of the forestry sector revitalization policies as part of the social forestry program. Beting Village formed a Hkm group to support the acceleration of economic development and improve the structure of the mangrove forest that had been reduced. This study aims to identify the socio-economic conditions of the members of the Banau Bisa Maju Cooperative, the level of participation of the members of the Banau Bisa Maju Cooperative in HKm management, and the institutional management of the Banau Bisa Maju Cooperative. The research method is using survey methods, interviews and observations. The total number of members of the Banau Bisa Maju cooperative is 74 respondents. Data analysis was done descriptively. The results showed that the social conditions of the members of the Banau Bisa Maju Cooperative have an interaction with forest resources by taking mangrove forest products. The economic condition of the cooperative members' welfare value is classified as good. Member participation in the Banau Bisa Maju Cooperative's business license has three aspects of success, namely the ecological aspect with an average score of 133 medium categories, the economic aspect an average score of 150 moderate categories and social aspects an average score of 155 moderate categories. Institutional management so that human resources are good to maintain the quality of their work in good and correct forest management techniques is the existence of coaching with counseling by the FMU.